2023
DOI: 10.1155/2023/6908757
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HBV and COVID‐19 Coinfection Model with Intervention Strategies

Shewafera Wondimagegnhu Teklu

Abstract: Coinfection of hepatitis B virus (HBV) and COVID-19 is a common public health problem throughout some nations in the world. In this study, a mathematical model for hepatitis B virus (HBV) and COVID-19 coinfection is constructed to investigate the effect of protection and treatment mechanisms on its spread in the community. Necessary conditions of the proposed model nonnegativity and boundedness of solutions are analyzed. We calculated the model reproduction numbers and carried out the local stabilities of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Different studies reveal that HBV is one of the microbial pathogenic viruses that commonly influencing the work of individuals’ liver and has been a cause for death of millions of individuals with its chronic stages liver cirrhosis and cancer 3 , 4 . HBV spreads in the population through direct and indirect transmission like with blood contact or fluids of infectious people or during child birth 2 , 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies reveal that HBV is one of the microbial pathogenic viruses that commonly influencing the work of individuals’ liver and has been a cause for death of millions of individuals with its chronic stages liver cirrhosis and cancer 3 , 4 . HBV spreads in the population through direct and indirect transmission like with blood contact or fluids of infectious people or during child birth 2 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The study investigates the fluctuation of the stochastic model HBV and COVID-19 co-epidemic disease-free equilibrium point using Lyapunov function method and the numerical results justifies the qualitative results. Teklu 2 formulated and examined the HBV and COVID-19 co-infection compartmental model to investigate the effects of some prevention and controlling strategies without applying optimal control theory. Li et al 52 constructed the generalized COVID-19 deterministic model to investigate the epidemiological characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [31] investigated the effect of model parameter values on the number of reproductions for HIV/AIDS disease by simulating various scenarios numerically and identified the most sensitive parameters. By applying the Castillo-Chavez criteria, the authors of [32] demonstrated that the disease-free equilibrium is asymptotically stable on a global scale whenever the associated reproduction number is less than one. Recently, the Castillo-Chavez criteria were again used by the authors of [33] to demonstrate the global stability of the models' disease-free equilibrium points.…”
Section: Introductionmentioning
confidence: 99%